Analisis Laporan Keuangan Dalam Menilai Kinerja Keuangan Pada Perusahaan Sektor Kesehatan Yang Terdaftar Di BEI Pada Periode 2018-2020 (Studi Kasus PT Darya-Varia Laboratoria Tbk) - Angga, Angga; Suartini, Sri; Sulistiyo, Hari (Tirtayasa Ekonomika, 2024)
The development of the pharmaceutical industry in Indonesia requires that every pharmaceutical company has the option of supervising and fostering its company in the implementation of the board in a more expert manner. The expertise of a company to generate profits is also fundamental, a company must be improved so that the company's performance is said to be good, because profit is one of the elements of financial statements as a tool to evaluate company performance. The exploration strategy used in this study is a quantitative technique. Quantitative information is an examination technique that relies on substantive information, research information as numbers to be measured using statistics as a calculation test tool, related to problems to achieve goals. The purpose of this study is to determine the financial performance of PT Darya-Varia Laboratoria Tbk, for the 2018-2020 period by utilizing the ratio of liquidity, solvency, activity, profitability. The results of the discussion took into account the financial performance of PT Darya-Varia Laboratoria Tbk, which consistently fluctuated and tended to decline at the end of 2020, this was due to a significant increase and decrease in financial statement items.